Chlamydia trachomatis causes the intracellular redistribution of MHC-I and impairs antigen presentation in dendritic cells - del Balzo, Diego Damián (2019)
Chlamydia trachomatis (CT) is the most frequent bacterial cause of sexually transmitted infections worldwide. This highly adapted intracellular bacterium has evolved multiple strategies to hide inside cells. However, little is known about the molecular mechanisms underlying CT evasion of the immune response. Dendritic cells (DCs) are the most efficient antigen-presenting cells of the immune system and, an essential link between innate and adaptive immunity. Therefore, DCs could play a key role in CT´s clearance. In this study, we analyzed in CT-infected DCs the process of cross-presentation, in which exogenous antigens are associated with MHC-I molecules to activate CD8+ T lymphocytes. By confocal microscopy and flow cytometry-based approaches, we observed, after chlamydial infection, a decrease in MHC-I molecules exposed at the plasma membrane while they are redistributed intracellularly. However, the total amount of MHC-I molecules did not change after infection, as assessed by western blot analysis. Finally, we found that CT-infected DCs were less efficient than non-infected ones to cross-present the model antigen Ovalbumin, as measured colorimetrically by the activation of the antigen-specific CD8+ T cell hybrid called B3Z. Altogether, these findings indicate that CT infection impairs antigen-cross presentation in DCs through the disturbance of MHC-I transport.